Burden between Undersupply and Overtreatment in the Care of Primary Spontaneous Pneumothorax - Hofmann, Hans-Stefan; Suttner, Tobias; Neu, Reiner; Potzger, Tobias; Szöke, Tamas; Grosser, Christian; Ried, Michael (The Thoracic and Cardiovascular Surgeon, 2018)
Background The optimal treatment of primary spontaneous pneumothorax (PSP) is still controversial. The purpose of this study was to analyze the incidence of recurrence, the recurrence-free time, and to identify risk factors for recurrence after PSP.Methods We performed a retrospective analysis of 135 patients with PSP who were treated either conservatively with a chest tube (n = 87) or surgically with video-assisted thoracoscopic surgery (VATS; n = 48) from January 2008 through December 2012.Results In this study, 101 (74.8%) male and 34 (25.2%) female patients were included with a mean age of 35.7 years. The indications for surgery included blebs/bullae in the radiological images (n = 20), persistent air leaks (n = 15), or the occupations/wishes of the patients (n = 13). A first ipsilateral recurrent pneumothorax (true recurrence) was observed in 31.1% of all patients (VATS: 6.25%, conservative: 44.8%). Including contralateral recurrence, the overall first recurrence rate was 41.3% (VATS: 14.6%, conservative: 57.5%). The recurrence-free time did not differ significantly between the treatment groups (p = 0.51), and most recurrences were observed within the first 6 months after PSP. Independent risk factors identified for the first recurrence were conservative therapy (p = 0.0001), the size of the PSP (conservative; p = 0.016), and a body mass index <17 (VATS; 0.022). The risk for second and third recurrences of PSP was 17.5 and 70%, respectively, for both treatment groups, but it was 100% after conservative therapy.Conclusion Surgery for PSP should be selected based on the risk factors and the patient's wishes to prevent first recurrences but also to avoid overtreatment. The treatment of first and subsequent PSP recurrences should be with surgery since conservative treatment is associated with a 100% recurrence rate.
Keywords: pneumothorax; primary spontaneous pneumothorax; recurrence; recurrence-free time; risk factors